2022
DOI: 10.3390/biom12070927
|View full text |Cite
|
Sign up to set email alerts
|

Cold Stress Induced Liver Injury of Mice through Activated NLRP3/Caspase-1/GSDMD Pyroptosis Signaling Pathway

Abstract: The body needs to generate heat to ensure basic life activities when exposed to cold temperatures. The liver, as the largest glycogen storage organ in the body and main heat-producing organ at rest, may play a role in chronic cold exposure. Recent studies suggested that pyroptosis plays a crucial role in liver diseases. However, the role of pyroptosis in cold stress-induced liver injury is not clear. Hence, in this study, we attempted to investigate the effects of chronic cold exposure on liver function, apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Our findings fit in with previous observations that inflammasome function is sensitive to temperature, both hypothermic and hyperthermic [ 19 , 25 , 28 , 29 , 30 , 31 , 32 , 33 ]. Notably, mutations in NLRP3 (first discovered as cryopyrin) are responsible for a group of disorders known as cryopyrin-associated autoinflammatory syndromes (CAPS) [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings fit in with previous observations that inflammasome function is sensitive to temperature, both hypothermic and hyperthermic [ 19 , 25 , 28 , 29 , 30 , 31 , 32 , 33 ]. Notably, mutations in NLRP3 (first discovered as cryopyrin) are responsible for a group of disorders known as cryopyrin-associated autoinflammatory syndromes (CAPS) [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
“…Karasawa et al recently discovered that mutant NLRP3 aggregates in the cold to nucleate inflammasome assembly and activation, explaining some of the characteristic cold-induced inflammation in a subtype of CAPS [ 19 ]. Consistently, severe hypothermia (4 °C) was associated with increased inflammasome activation in a model of cold-stress-induced liver injury in mice [ 30 ]. However, as opposed to severe hypothermia (4 °C), several studies have shown that mild hypothermia (32–34 °C) inhibits inflammasome function in WT cells and rats [ 29 , 31 , 33 ].…”
Section: Discussionmentioning
confidence: 95%
“…Early data have certainly established that cold stress in livestock is common in winter ( Young, 1983 ). Recent studies have shown that long-term exposure of animals to low temperatures inhibits growth, along with adverse effects such as inflammation ( Liu et al., 2019 , 2022 ; Luo et al., 2019 ). As the building blocks of peptides and proteins, AA are necessary for all life-sustaining processes.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive data have confirmed that cold limits animal growth and increases feed intake ( Bayril et al., 2020 ; Toghiani et al., 2020 ). More worryingly, long-term cold exposure induces oxidative stress and inflammation in organs, even causing death in animals ( Liu et al., 2019 , 2022 ; Luo et al., 2019 ). Adaptation to low ambient temperature is one of the mechanisms vital to the survival of mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, GO enriched to “heat shock protein binding, GO:0031072”, which is associated with heat shock protein binding activity ( Yue et al, 2020 ). It has been reported that the expression of heat shock proteins is increased in mice exposed to cold stimuli ( Liu et al, 2022b ). This phenomenon has also been observed in goats and the expression of the heat shock protein 70 gene is breeds specific ( Banerjee et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%